Does parasitemia level increase the risk of acute kidney injury in patients with malaria? Results from an observational study in Angola - Euclides Nenga Manuel Sacomboio; Cruz dos Santos Sebastião; Adelino Tchilanda Tchivango; Roberto Pecoits-Filho; Viviane Calice-Silva (Scientific African, 2020)
Background: The incidence of Acute Kidney Injury (AKI) due malaria has increased and in low and middle-income countries with negative impact in the death and hospitalization. The aim of this study was to evaluate AKI incidence and effects of parasitemia levels in the kidney function of patients hospitalized with malaria in Josina Machel hospital from March to May 2016. Methods: A longitudinal, prospective and observational study was performed with 135 patients hospitalized with malaria during the study period. Patients were followed-up and monitored by measurements of serum creatinine (SCr) and Blood Urea Nitrogen (SUr) for a period between 2 and 4 days. The diagnosis of AKI and Acute Kidney Disease (AKD) was carried out according to Kidney Disease Improving Global Outcomes (AKI-KDIGO) criteria. Additionally, information regarding blood parasite concentration and antimalarial treatment used was collected for all patients. Results: A total of 86 patients fulfilled the inclusion criteria and were enrolled in the study. From which, 61/86 (71%) were males, with mean age of 21.3 years. A total of 36/86 (42%) were with AKI in different stages. Interestingly, it was observed that high and hyper parasitemia were present in patients with AKI. The quinine was the anti-malarial most used in patients with AKI (54%). The hospitalization length 21/40(78%) and mortality 7/8(88%) rate was higher in patients with high and hyper parasitemia and AKI. Conclusion: We observed high and hyper parasitemia in patients with different stages of AKI. The hospitalization length and mortality rates were higher in this group of patients, especially in the more advanced stages of kidney injury. Further studies are needed to depth the consistency of the relationship between parasitemia and kidney injury to help control the emergence of kidney injury of the malaria patients in Angola. Keywords: Malaria, Parasitemia, Acute kidney Injury, Luanda, Angola